طريقة منهجية لربط شبكة الإحداثيات المحلية في منطقة جوبة دريوس العقارية بشبكة الإحداثيات العامة العقارية في سورية - فحصة اياد; يازجي سومر (Latakia University Journal -Engineering Sciences Series, 2016)
يتضمن البحث دراسة جيوديزية لشبكة المثلثات العقارية المحلية في منطقة صلنفة، واقتراح حل من أجل ربط الشبكة المحلية بالشبكة العقارية العامة في سورية.يعتمد العمل على مقارنة نتائج التحويل ثنائي الأبعاد،بحيث يتم اختيار التحويل الأمثل الذي يتلافى حدوث تداخلات بين المناطق والمخططات العقارية، ويقلل من تشوهات الشبكة بعد تحويلها(انزياح، دوران، مقياس). في البداية تم التطرق إلى تاريخ انشاء الشبكة الجيوديزية في منطقة صلنفة ومراحل تنفيذها، ومشاكلها الهندسية، وثم إلى طرق التحويل المستخدمة في الربط، وتطبيقها على الشبكة، واختيار التحويل الأفضل، وتعيين بارمترات التحويل المناسبة.وتم اقتراح حل يعتمد على تقسيم الشبكة إلى ثلاث قطاعات،بحيث يقلل تشوه الشبكة الناتج عن التحويل في كل قطاع. تم اعداد برنامج حاسوبي لتنفيذ التحويل المُقترح وربط نقاط الشبكة المحلية باستخدام لغة البرمجة C#. وتم التحقق من بارمترات التحويل الناتجة بمقارنة القياسات الخطية المحسوبة من الاحداثيات الناتجة عن التحويل مع القياسات الخطية الموجودة في دفاتر رصد الشبكة، وبإجراء قياسات حقلية لبعض النقاط الموجودة وحساب احداثياتها ومقارنتها مع الاحداثيات المحسوبة عن التحويل. Search includes the geodetic study local network triangulation real estate in Slenfeh area, and propose a solution for the local network linking public real estate network in Syria based on a comparison of the 2D-Transformation results so as to choose the optimal conversion which avoids the occurrence of interactions between regions and schemes real estate and reduces distortions network after conversion (shift, rotation, scale). At first been touched to date geodesic network set up in Slenfeh region and the stages of execution, and the problems of engineering, and then to the transformation methods used in the link, and apply them to the network, and choose the best conversion, and set parameters optimal transformation, have been proposed solution depends on the network is divided into three segments so that Network least deformation resulting from the transformation in each sector. A computer program that has been prepared for the implementation of the transformation and linking local grid points by using the C # programming language. It has been verified the resultant transformation parameters by comparing linear measurements calculated from coordinates resulting from the transformation with linear measurements in the network observation records, and execution field measurements of some of the points and calculate its coordinates and compare it with the coordinates calculating fromtransformation.